(untitled) (Research, Society and Development, 2022)
Transcranial direct current stimulation (tDCS) is a neuromodulation technique that causes alterations in the synthesis of several proteins, including cytokines (e.g., Interleukins). Pro-inflammatory cytokines are associated with the presence of pain and their reduction occurs in several pathologies. The aim of this study was to investigate the effects of tDCS on the variation of tissue and serum blood levels of pro-inflammatory cytokines and its relationship with behavioral changes, through a systematic review. PubMed, Embase and Lilacs database searches were performed for articles published in all languages ​​before October 1, 2020. The search was based on the keywords "Transcranial Direct Current Stimulation" or "tDCS" and "IL-1alpha " or "IL-1Beta" or "IL-6" or "IL-8" or "IL-17" or "Tumoral necrosis factor alpha" or "TNF-alpha". The systematic review protocol was registered in PROSPERO (CRD42021283417). Initially, 416 studies were identified in the electronic databases, of which 40 were eliminated because they were duplicates. Of the remaining 376, 358 were excluded after analyzing the title and abstract (selection stage) and 09 were excluded after a complete reading. Nine studies were considered for evaluation. The results demonstrate that tDCS can alter the levels of pro-inflammatory cytokines and modify behaviors in animals, however these findings are variable. Still, the cause and effect relationship between cytokine levels and behavioral changes found was not conclusive. Further studies are needed to establish the mechanisms involved in the action of tDCS on the levels of pro-inflammatory cytokines.